Translation Methods of Vernacular Literature Works : Take Those of Jia Pingwa as an Example - Ji, Ni (Pacific International Journal, 2024)
Translation is a cultural exchange, not just a linguistic transformation. Foreign translation of vernacular literature works is also an important way to promote the Chinese folk culture. However,the cultural omission hinders foreign readers from gaining a deeper understanding of Chinese vernacular culture.Therefore, this thesis selects the English translation of Turbulence as the object of study, aiming to explore the translation strategies of vernacular language such as the names of people, and the names of Shaanxi snacks present in the work. For the purpose, the translator carefully collates the names of people and special snacks in Shaanxi that appear in the work. Besides, the author will combine the above examples to make an in-depth analysis of the translation when writing the paper. The following conclusions have been drawn: Firstly, when the author of the original wants to highlight the uniqueness of Chinese folk culture, she should use domesticating translation, because this kind of translation strategy can retain the characteristic content of the original. In addition, if the author wants foreign readers to understand the local snacks, the translator should use the direct translation. The direct translation method can give the Western readers a basic understanding of the main ingredients used in the special snacks.